Correlação anatômica-comportamental-farmacológica dos parâmetros de dor neuropática crônica experimental - Alves, Nilza Dutra (2004)
Pain is a very common symptom in patients. It may involve somatic, visceral and neural structures. Neuropathic pain may be chronic with undefined mechanism and that is a challenge for therapy. With the aim of contributing to understand mechanisms and rational therapy for chronic neuropathic pain, we developed this work in order to do an anatomo-pharmacological-behavioral correlation (1) by quantifying spontaneous and induced behaviors, (2) administrating drugs with action on the GABA system, Ca++ and Na+ channels and (3) stimulating and inhibiting the periaqueductal region (PAG). For this, 75 Wistar male and female rats, divided into 10 groups, were used. As model of neuropathic pain, the constriction of sciatic nerve was used. The rats were observed during 30 days and, at the 31st day, drugs were administered. For stimulation and inhibition of the PAG, a cannula was inserted in it (Groups VII, IX and X of rats). The spontaneous behaviors were observed in open field and thermal tests were carried out to induce pain behaviors. The pharmacological tests with gabapentin, vigabatrin, lamotrigin and morphine were carried out in Groups IV to VII. The stimulation with morphine and inhibition with morphine/naloxone and lidocain in the PAG were carried out in Groups VIII, IX and X of rats. The results showed that gabapentin, vigabatrin, lamotrigin and morphine decreased significantly the scratching and biting behaviors, as well as reverted allodynia and hyperalgesia. In addition, morphine administered in PAG reduced significantly the scratching and biting behaviors, and this effect was reverted by naloxone. Lidocaine, in its side, did not change the increased scratching and biting behaviors. Our results may conclude that the behaviors suggestive of chronic neuropathic pain (scratching and biting) are inhibited by drugs with gabaergic action, blocking effect on Ca++ and Na+ channels and through PAG stimulation with morphine, as well as PAG inhibition with morphine/naloxone and lidocain. These results reinforce the interpretation of these behaviors as suggestive symptoms of chronic neuropathic pain in animals.